2011
DOI: 10.1007/s12028-011-9594-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Monitoring of Vasospasm and Delayed Cerebral Ischemia: A Review and Assessment of the Literature

Abstract: Delayed cerebral ischemia (DCI) after subarachnoid hemorrhage can be evaluated using clinical assessment, non-invasive and invasive techniques. An electronic literature search was conducted on English-language articles investigating DCI in human subjects with subarachnoid hemorrhage. A total of 31 relevant papers were identified evaluating the role of clinical assessment, transcranial Doppler, computed tomographic angiography, and computed tomographic perfusion. Clinical assessment by bedside evaluations is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 32 publications
0
80
0
1
Order By: Relevance
“…35 Zhang et al showed that quantitative data from CTP imaging can be used to prospectively determine if the vasospasm is severe enough to cause symptomatic changes in the patient. 40 Early CTP imaging can also efficaciously stratify patients at risk for developing DCI.…”
Section: Cta and Ct Perfusionmentioning
confidence: 99%
“…35 Zhang et al showed that quantitative data from CTP imaging can be used to prospectively determine if the vasospasm is severe enough to cause symptomatic changes in the patient. 40 Early CTP imaging can also efficaciously stratify patients at risk for developing DCI.…”
Section: Cta and Ct Perfusionmentioning
confidence: 99%
“…Much of the outcome is determined by secondary complications many of which are treatable if diagnosed in a timely fashion. Between 20-40% of SAH patients either clinically deteriorate or have evidence of new ischemia on repeat brain imaging from vasospasm, together termed delayed cerebral ischemia [5,42,43]. Delayed cerebral ischemia is associa ted with worse outcome [5], but may be particularly challenging to diagnose in the comatose patient [6].…”
Section: Clinical Scenario: Delayed Cerebral Ischemia After Subarachnmentioning
confidence: 99%
“…Currently, the only serial detection method in routine use is transcranial Doppler ultrasonography (TCD). Although mean blood fl ow velocities of > 120 cm/s are around 60-70% sensitive to changes in the proximal middle cerebral artery (MCA), this cut-off is less reliable (and less well studied) for other territories and does not include the distal vasculature [42]. When used daily, TCDs have been 60-70% sensitive for delayed cerebral ischemia with limited predictive value; they also exhibit frequent false negatives or false positives [44].…”
Section: Clinical Scenario: Delayed Cerebral Ischemia After Subarachnmentioning
confidence: 99%
“…However, the values of the pulsatility index and resistance index were not significantly different between the two groups. Correct interpretation of the pulsatility index is complex, because it depends not only on cerebrovascular resistance but also on several systemic and cerebral variables (11,12). The Rotterdam Study reported that increased mild-to-moderate cerebral blood flow velocity was due to diffuse atherosclerosis or vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%